PENINGKATAN NILAI KUAT GESER BETON DENGAN MENGGUNAKAN FIBER LOKAL KAWAT BENDRAT BENTUK “U” DAN “Z” DENGAN 3 VARIASI CAMPURAN: indonesia - Juanita, Juanita (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2022)
Concrete is the main basic material used for planning and designing building structures and is widely used as a building material. One of the efforts to improve the unfavorable properties of the concrete in this case is to add bendrat wire fiber to the concrete mix. In this study, bendrat wire fibers in the shape of "U" and "Z" were used with variations in the addition of fiber in the concrete mix of 0.5%, 0.75% and 1% of the cement weight. The bendrat wire used has a length of 60 mm and a diameter of 1 mm. The test specimens were made in the form of a double-L beam with dimensions (200 x 150 x 300) mm as many as 21 pieces. Double-L beam testing was carried out at the age of 28 days using a Compression Testing Machine (CTM). From the results of the research, the highest shear strength of concrete was obtained in "U" shape bentrat wire fiber concrete with 1% bendrat wire percentage (BF3) with an average value of 6.00 MPa or an increase in concrete shear strength of 46.33% compared to Normal Concrete (BN). The value of the shear strength of the double-L beam with "U" shape bendrat wire fiber is higher than the value of the double-L shear strength beam with "Z" shape bendrat wire fiber although the difference in the shear strength value is not too significant. The addition of "U" and "Z" bentrat wire fibers can reduce cracks in the concrete.